Electronic structure of the Zn(O, S)/Cu(In, Ga)Se2 thin‐film solar cell interface. (10th March 2016) - Mezher, Michelle; Garris, Rebekah; Mansfield, Lorelle M.; Horsley, Kimberly; Weinhardt, Lothar; Duncan, Douglas A.; Blum, Monika; Rosenberg, Samantha G.; Bär, Marcus; Ramanathan, Kannan; Heske, Clemens
Abstract: The electronic band alignment of the Zn(O, S)/Cu(In, Ga)Se2 interface in high‐efficiency thin‐film solar cells was derived using X‐ray photoelectron spectroscopy, ultra‐violet photoelectron spectroscopy, and inverse photoemission spectroscopy. Similar to the CdS/Cu(In, Ga)Se2 system, we find an essentially flat (small‐spike) conduction band alignment (here: a conduction band offset of (0.09 ± 0.20) eV), allowing for largely unimpeded electron transfer and forming a likely basis for the success of high‐efficiency Zn(O, S)‐based chalcopyrite devices. Furthermore, we find evidence for multiple bonding environments of Zn and O in the Zn(O, S) film, including ZnO, ZnS, Zn(OH)2, and possibly ZnSe. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The electronic band alignment of the Zn(O, S)/Cu(In, Ga)Se2 interface in high‐efficiency thin‐film solar cells is found to exhibit a conduction band offset of 0.09 ± 0.20 eV, that is, an essentially flat (small‐spike) alignment allowing for largely unimpeded electron transfer and forming a likely basis for the success of high‐efficiency Zn(O, S)‐based chalcopyrite devices. Furthermore, evidence for multiple bonding environments of Zn and O in the Zn(O, S) film is found, including ZnO, ZnS, Zn(OH)2, and possibly ZnSe.